Proteomic data of seminal plasma and spermatozoa of four purebred dogs - Araujo, Michelle Silva [UNESP]; Oliveira Henriques Paulo, Otavio Luis de [UNESP]; Paranzini, Cristiane Sella [UNESP]; Scott, Caroline [UNESP]; Codognoto, Viviane Maria [UNESP]; Freitas Dell'Aqua, Camila de Paula [UNESP]; Papa, Frederico Ozanam [UNESP]; Souza, Fabiana Ferreira de [UNESP] (Elsevier B.V., 2020)
Semen contains several proteins that are important to fertilization and to identify reproductive failures. There are proteins that are specie-specific expressed, although differs among several breeds. This article provides experimental data describing the protein profile of seminal plasma and spermatozoa of four healthy purebred dogs: Golden Retriever (n=3), Bernese Mountain Dog (n=4), Great Dane (n=3), and Maremmano-Abruzzese Sheepdog (n=3), housed at Sao Paulo state, Brazil. Semen samples were collected by manual stimulation of the penis in a presence of a teaser bitch, when possible. The seminal plasma and sperm cells were separated by centrifugation and prepared for mass spectrometry. The gene ontology annotation of the proteins found is described. This is the first time that proteomic profile of the semen of pure-bred dogs is described. These data are a valuable resource to improve the biotechnologies of reproduction applied to canid species. (C) 2020 The Author(s). Published by Elsevier Inc.
Keywords: Proteomic; Mass spectrometry; Purebred dog; Semen